The Influence of Financial Literacy, Risk Tolerance and Return on Investment Decisions Among Capital Market Study Group Students at Jambi University - Feby Anisya Nabila; Achmad Hizazi; Ratih Kusumastuti (Greenation Research & Yayasan Global Resarch National, 2025)
This study examines the influence of financial literacy, risk tolerance, and return on investment decisions among Capital Market Study Group (KSPM) students at Jambi University. Using quantitative methods with multiple linear regression analysis on 73 respondents who are active KSPM members with investment experience, the results show that simultaneously, financial literacy, risk tolerance, and return significantly influence investment decisions (F = 17.032, sig. 0.000). Partially, risk tolerance has the most dominant positive and significant effect (B = 2.175, sig. 0.000), return also shows positive and significant effect (B = 1.578, sig. 0.003), while financial literacy shows no significant effect (B = -0.110, sig. 0.897). The research contributes to behavioral finance theory by demonstrating that psychological factors (risk tolerance) are more influential than cognitive factors (financial literacy) in student investment decisions.